Gut Microbiota-Bile Acid Crosstalk in Diarrhea-Irritable Bowel Syndrome. (12th November 2020) - Zhan, Kai; Zheng, Huan; Li, Jianqing; Wu, Haomeng; Qin, Shumin; Luo, Lei; Huang, Shaogang
Abstract : The occurrence of diarrhea-predominant irritable bowel syndrome (IBS-D) is the result of multiple factors, and its pathogenesis has not yet been clarified. Emerging evidence indicates abnormal changes in gut microbiota and bile acid (BA) metabolism have a close relationship with IBS-D. Gut microbiota is involved in the secondary BA production via deconjugation, 7 α -dehydroxylation, oxidation, epimerization, desulfation, and esterification reactions respectively. Changes in the composition and quantity of gut microbiota have an important impact on the metabolism of BAs, which can lead to the occurrence of gastrointestinal diseases. BAs, synthesized in the hepatocytes, play an important role in maintaining the homeostasis of gut microbiota and the balance of glucose and lipid metabolism. In consideration of the complex biological functional connections among gut microbiota, BAs, and IBS-D, it is urgent to review the latest research progress in this field. In this review, we summarized the alterations of gut microbiota in IBS-D and discussed the mechanistic connections between gut microbiota and BA metabolism in IBS-D, which may be involved in activating two important bile acid receptors, G-protein coupled bile acid receptor 1 (TGR5) and farnesoid X receptor (FXR). We also highlight the strategies of prevention and treatment of IBS-D via regulating gut microbiota-bile acid axis, including probiotics, fecal microbiota transplantation (FMT), cholestyramine, and the cutting-edge technology about bacteria genetic engineering.